2018
DOI: 10.2355/isijinternational.isijint-2018-301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B on Growth of Recrystallized Grain of Ti-added Ultra-low Carbon Cold-rolled Steel Sheets

Abstract: The effect of boron (B) on the recrystallization behavior, in particular the growth of the recrystallized grain into the unrecrystallized grain, of titanium (Ti) added interstitial atom free (IF) steel sheets was studied from the viewpoint of the solute-drag effect considering the interaction between B and Ti atoms. The growth rate of the recrystallized grain at 5% fraction recrystallized decreased with increasing the B content. Furthermore, the decrease became more pronounced in the B added steels with the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Moreover, it was confirmed that the amount of Ti segregation increases as the amount of B increases, which implies that B and Ti have a tendency to cosegregate. The co-segregation of B and Ti was also verified by the first principle calculation for the symmetrical tilt boundary of α-Fe(111)Σ3 ½1 10 [26]. The first principle calculation has also been conducted for the interaction between B and other substitutional transition metals in an α matrix.…”
Section: Segregation Of Solute Elements At the Interface Between Recrmentioning
confidence: 74%
See 4 more Smart Citations
“…Moreover, it was confirmed that the amount of Ti segregation increases as the amount of B increases, which implies that B and Ti have a tendency to cosegregate. The co-segregation of B and Ti was also verified by the first principle calculation for the symmetrical tilt boundary of α-Fe(111)Σ3 ½1 10 [26]. The first principle calculation has also been conducted for the interaction between B and other substitutional transition metals in an α matrix.…”
Section: Segregation Of Solute Elements At the Interface Between Recrmentioning
confidence: 74%
“…However, it has been difficult to determine the actual state of the alloying elements in the moving interface. Recently, atom probe tomography (APT) has revealed the actual state of alloying elements in view of the solute drag effect using B bearing Ti-IF steel [25,26]. Figure 7 shows that .…”
Section: Segregation Of Solute Elements At the Interface Between Recrmentioning
confidence: 99%
See 3 more Smart Citations